2019
DOI: 10.1007/s40204-019-0108-7
|View full text |Cite
|
Sign up to set email alerts
|

A silk fibroin/decellularized extract of Wharton’s jelly hydrogel intended for cartilage tissue engineering

Abstract: A hybrid hydrogel was obtained from decellularized extract from Wharton’s jelly (DEWJ) and silk fibroin (SF) and characterized for cartilage tissue engineering. Wharton’s jelly was used due to its similarity with articular cartilage in extracellular matrix composition. Also, silk fibroin has good mechanical properties which make this construct appropriate for cartilage repair. Decellularization of Wharton’s jelly was verified by DAPI staining, DNA quantification, and PCR analysis. Then, the biochemical composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 48 publications
2
38
0
7
Order By: Relevance
“…Wharton's jelly from umbilical cord is becoming increasingly proposed as an ideal source for obtaining scaffold useful for tissue engineering application (Beiki et al, 2017;Basiri et al, 2019). WJ is easy to obtain as biological waste material, is non-immunogenic, and its use presents no ethical concerns (Forraz and McGuckin, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wharton's jelly from umbilical cord is becoming increasingly proposed as an ideal source for obtaining scaffold useful for tissue engineering application (Beiki et al, 2017;Basiri et al, 2019). WJ is easy to obtain as biological waste material, is non-immunogenic, and its use presents no ethical concerns (Forraz and McGuckin, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…WJ contains abundant collagenic structural proteins (collagen I, III, VI, and XII), other ECM components such as fibronectin, lumican, heparin sulfate, and growth factors (TGFβ, FGFβ, VEGF) (Jadalannagari et al, 2017). It has been demonstrated that DWJM is able to retain many chemotactic factors and soluble bioactive factors positively affecting cell viability and function (Basiri et al, 2019). Therefore, for these different reasons DWJM has been proposed as potential therapeutic agent in many areas (Jadalannagari et al, 2017;Kehtari et al, 2019;Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests significant loss of matrix components, likely glycosaminoglycans with decrease of typical intense vibrational bands observed in N-UC, also described in the literature, at 1550 cm −1 for carboxylate group, 1400 cm −1 for acetyl amino group and 1050 cm −1 sulfate group. 19,20 Real-time PCR Changes of chondrogenic mRNA markers (Col II, Sox9, and Aggrecan) in both tissue and gelatin cells-scaffolds were evaluated by real-time RT-PCR ( Fig. 5).…”
Section: Scaffold Fabrication and Characterizationmentioning
confidence: 99%
“…15,16 Wharton's jelly matrix is a connective tissue that encircles the vessels of the umbilical cord and is covered by a simple amniotic epithelium. 16,17 Decellularized Wharton's jelly (DEWJ) is a natural ECM-derived material that can be used to construct a biocompatible matrix. It contains glycosaminoglycans (GAGs), especially hyaluronic acid (HA), collagens II, VI, and XII, fibronectin I and lumican.…”
Section: Introductionmentioning
confidence: 99%